2014
DOI: 10.1073/pnas.1405528111
|View full text |Cite|
|
Sign up to set email alerts
|

Noninvasive in vivo monitoring of tissue-specific global gene expression in humans

Abstract: Significance Circulating cell-free RNA in the blood provides a potential window into the health, phenotype, and developmental programs of a variety of human organs. We used high-throughput methods of RNA analysis such as microarrays and next-generation sequencing to characterize the global landscape of circulating RNA in human subjects. By focusing on tissue-specific genes, we were able to identify the relative contributions of these tissues to circulating RNA and monitor changes during tissue develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
261
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(278 citation statements)
references
References 57 publications
17
261
0
Order By: Relevance
“…Previous maternal plasma transcriptomic profiling studies have shown that certain trophoblast-specific transcripts and the overall fractional placental contribution increase with gestation (20,39,40). The fraction of fetal-derived RNA increases from only 3.7% in early pregnancy to 11.28% in late pregnancy (19,20).…”
Section: Noninvasive Elucidation Of Placental Cellular Dynamics Durinmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous maternal plasma transcriptomic profiling studies have shown that certain trophoblast-specific transcripts and the overall fractional placental contribution increase with gestation (20,39,40). The fraction of fetal-derived RNA increases from only 3.7% in early pregnancy to 11.28% in late pregnancy (19,20).…”
Section: Noninvasive Elucidation Of Placental Cellular Dynamics Durinmentioning
confidence: 95%
“…Significantly elevated levels of total cell-free DNA and selected placenta-specific RNA transcripts have also been reported in the maternal plasma of women with PE (8)(9)(10)(11), restricted fetal growth (12), and preterm birth (13)(14)(15), supporting a role for cell-free nucleic acids as a noninvasive tool for placental monitoring. Previous studies have attempted to provide a comprehensive assessment of maternal plasma nucleic acids by microarray analysis, massively parallel transcriptomic, or methylomic sequencing (16)(17)(18)(19)(20)(21)(22). Several groups have explored the use of fetal-specific DNA polymorphisms, organ-specific DNA methylation (21), nucleosome footprinting (23), DNA fragmentation patterns (24), and tissuespecific RNA transcripts (19,20) to isolate the placental signal in the pool of circulating cell-free fetal nucleic acids and obtain changes of overall placental contribution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have shown that such an approach is possible 12,13 . In 2014, for example, Quake's team examined blood samples from pregnant women using RNA-seq, in combination with other methods, to detect RNAs that probably originated in the fetus and placenta 12 .…”
Section: Full Transcriptmentioning
confidence: 99%
“…In 2014, for example, Quake's team examined blood samples from pregnant women using RNA-seq, in combination with other methods, to detect RNAs that probably originated in the fetus and placenta 12 . They could track the ebbs and flows of transcripts through all three trimesters, including the activity of genes that are crucial for normal brain development.…”
Section: Full Transcriptmentioning
confidence: 99%